2010
DOI: 10.2341/09-133-c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Indirect Composite Restorations at Baseline and 36 Months After Placement

Abstract: all success rates for marginal integrity were 70.7% for Grandio and 71.8% for Admira; both were evaluated 36 months after placement. The results have shown that the indirect restorations were acceptable after 36 months, which indicates a 100% success rate. Over 36 months, no statistically significant differences were noted between the two materials. Indirect resin composite restorations represent a good therapy choice for severely damaged teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 31 publications
3
27
0
4
Order By: Relevance
“…This technique simplifies the production of indirect restorations and Even though there is no report on the comparison of CAD/CAM resin composite partial crowns and direct posterior resin composite restorations, there are many clinical studies comparing direct and indirect resin composite restorations that found no differences between the clinical success of these restorations. [22][23][24] In accordance with our results, Dukic et al 25 term clinical trials. [14][15][16] In this study, no reduction was observed in any criteria throughout the whole evaluation periods in CAD/CAM group.…”
Section: Discussionsupporting
confidence: 92%
“…This technique simplifies the production of indirect restorations and Even though there is no report on the comparison of CAD/CAM resin composite partial crowns and direct posterior resin composite restorations, there are many clinical studies comparing direct and indirect resin composite restorations that found no differences between the clinical success of these restorations. [22][23][24] In accordance with our results, Dukic et al 25 term clinical trials. [14][15][16] In this study, no reduction was observed in any criteria throughout the whole evaluation periods in CAD/CAM group.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with previous reports of success rates of 80 -100% for composite inlays following similar observation periods (12-14) ( Table 4). Previous studies showed that the physical and mechanical properties of resin composites are greatly affected by the degree of conversion (DC) in the cross-linked polymeric system (15).…”
Section: Discussionsupporting
confidence: 93%
“…Ceramic ones are resistant to compressive forces but are susceptible to tensile stresses and more prone to fracture then are composite onlays [3,16,17]. Nine clinical studies have evaluated ceramic and composite materials for onlays [18][19][20][21][22][23][24][25][26]. Yet, we can draw no definite conclusions on the best material for onlay from these studies.…”
Section: Methodsmentioning
confidence: 83%